Human–Nature Relations in Nusantara Cosmology and Ecological Solutions - Arif Hidayat; Noor Abdullah; Halima Sani; Sahrani Somadayo; M. Ainur Ridlo (Mahkota Science Publishers, 2026)
Nusantara cosmology proposes a radical reversal of the human–nature relationship, positioning humans not as the centre of power but as an ethical part of a cosmic web of life that demands existential responsibility for the sustainability of the universe. This study aims to systematically analyse the human–nature relationship within Nusantara cosmology, identify its underlying foundational principles, and explore its potential to contribute to sustainable ecological solutions, using a qualitative approach grounded in critical ethnography. The findings reveal that the modern ecological crisis is fundamentally a crisis of perspective. Thus, the reconstruction of Nusantara cosmology is not merely a cultural endeavour, but an epistemological intervention with the potential to reshape the foundations of the human–nature relationship by positioning nature as a meaningful subject demanding ethical, legal, and political recognition. Through the integration of the concept of nature’s subjectivity, the revitalisation of rituals as social technologies, and the reinterpretation of cosmic values within the framework of public policy, this study implicitly challenges the dominance of the exploitative development paradigm whilst offering a new horizon for an ecological ethics that is more relational, contextual, and transformative, albeit still facing the tension between modern rationality and cultural legitimacy, as well as limitations in the institutionalisation of spiritual values within formal systems.